Can patient and carers' experiences shape services?. Issue 3 (5th October 2018) - Parry, Laura
Abstract : Dementia is an increasingly recognised medical condition which, towards its later stages, leads to the manifestation of symptoms that often require palliation. Hospice admission for patients with dementia has been shown to increase caregiver satisfaction. Yet, admission can be harmful for the patient. This feature follows the case of one patient, Mr Smith, who was admitted to Royal Trinity Hospice (RTH) for symptom control, along with providing respite for his carers. Shortly into Mr Smith's admission, he became increasingly agitated and was ultimately discharged home. After investigating the cause of early discharge, it was concluded that the newly built, modernised private rooms were in fact very dissimilar to the homes of patients with dementia. Adapting the clinical environment to improve patient and carer satisfaction has been explored in numerous studies. Significant amendments used by hospices and care homes include bold signs and natural lighting to facilitate way-finding, in addition to vintage furnishings to create a sense of familiarity. Taking recent evidence into consideration, RTH designed a new dementia-friendly bay situated on the ground floor of its inpatient unit. Since then, many other patients with dementia have been admitted to the hospice, one being Mr Thomas. Unlike Mr Smith, Mr Thomas was much more relaxed during his admission and his wife commented on how pleased she was with his care. This feature demonstrates the importance of being receptive to feedback and identifying the need for change.